Multiplisitas Wajah Rahim: Karya Seni sebagai Narasi Feminis (Refleksi atas Pameran Tunggal Dewi Candraningrum “Dokumen Rahim”) - Ratna Noviani (Universitas Gadjah Mada, 2016)
The term ‘womb’ is an organ in the lower abdomen of female body, which is particularlyassociated with pregnancy. Metaphorically, womb is perceived as the origination ofthings that are brought to life with the pour of an intense feeling of affection. The wombis an act of creation, a document of maternal procreation. This article is a refl ectivereading of ‘Womb Document’, a solo painting exhibition by a feminist female artist,Dewi Candraningrum. She tries to move away from what is considered aspure, selfreferentialand apolitical art. Artwork is a feminist narration. Clusters of her mostlyfemale portraiture paintings and sketches represent multiple faces of womb, which havebeen resided in the margins of hegemonic discourse. She uses aesthetic conventionsin her visual artworks, which are different from those applied in the canon. Dewi hasconsidered visual artworks as part of political arts, which should take a side andemancipate the considered Others.